ANALISIS FAKTOR MOTIVASI YANG MEMPENGARUHI PRESTASI BELAJAR SISWA PADA BIDANG STUDI MATEMATIKA DI SEKOLAH MENENGAH PERTAMA NEGERI 1 NAMLEA - Zakaria, Yusran; Umanailo, M. Chairul Basrun; Lisaholit, Syafa; Chamidah, Dina (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This study aims to determine the effect of motivation on mathematics learning achievement of students at Namlea 1 Middle School. This research is a form of research